The challenges of Peruvian foreign policy regarding Western Sahara - Saavedra Calderón, José Antonio (2024)
On August 18, 2022, the Ministry of Foreign Affairs of Peru, through Official Statement 004-22, announced two decisions of its then Foreign Minister. The first was the withdrawal of recognition of the Sahrawi Arab Democratic Republic (hereinafter "SADR") and the severance of all relations. The second es the expression of value and respect for the territorial integrity of the Kingdom of Morocco, its sovereignty, and the autonomy plan on the latter’s regional dispute with the Sahrawi people. This fact is an opportunity to analyse Peru's foreign policy, i.e., Peru´s traditional position regarding the R.A.S.D., and the changes that have taken place based on the political-diplomatic, economic-commercial criteria, at a time of a multipolar world, witnessing a intensity geopolitical confrontation. Thus, the objective is to explain the meaning and scope of both decisions for Peru, and the challenges they represent for national interests. Likewise, through a descriptive and analytical method, Peru's challenges are explained within the framework of gestation of a new international order.